A Probabilistic Fixed Point Result Using Altering Distance Functions - Claudia Zaharia; Nataša Ćirović (Journal of Function Spaces)
We prove a general fixed point theorem in Menger spaces for mappings satisfying a contractive condition of Ćirić type, formulated by means of altering distance functions. Thus, we extend some recent results of Choudhury and Das, Miheţ, and Babačev and also clarify some aspects regarding a theorem of Choudhury, Das, and Dutta.